Solid electrolytic capacitor element and solid electrolytic capacitor
By using thermogravimetric analysis optimized solid electrolytes and aromatic compound dopants in solid electrolytic capacitors, the problem of decay of solid electrolytic capacitors under high temperature environments is solved, and high thermal stability and reliability are achieved.
Patent Information
- Application Number
- CN202180032435.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-05-15
- Filing Date
- 2021-04-30
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2041-04-30
AI Technical Summary
Solid electrolytic capacitors are prone to decomposition of dopant components and deterioration of conductive polymers under high temperature environments, resulting in reduced conductivity and deterioration of performance.
By using a solid electrolyte optimized based on thermogravimetric analysis in the solid electrolyte layer, it is ensured that after it is maintained at 180°C for 20 minutes, the weight reduction rate at 260°C is less than 3%. In addition, using a dopant component containing an aromatic compound, the aromatic compound has electron-absorbing and electron-donating functional groups, which enhances its thermal stability and hydrolysis resistance.
High thermal stability and reliability of solid electrolytic capacitor components and capacitors are achieved, dopant decomposition and conductive polymer oxidation deterioration in high temperature environments are suppressed, and the reduction of electrostatic capacity and the increase of equivalent series resistance are reduced.
Smart Images

Figure CN115485800B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a solid electrolytic capacitor element and a solid electrolytic capacitor. Background Art
[0002] The solid electrolytic capacitor comprises a solid electrolytic capacitor element, a resin outer casing or a shell that seals the solid electrolytic capacitor element, and an external electrode electrically connected to the solid electrolytic capacitor element. The solid electrolytic capacitor element comprises an anode body, a dielectric layer formed on the surface of the anode body, and a cathode portion that covers at least a portion of the dielectric layer. The cathode portion comprises a solid electrolyte layer that includes a conductive polymer and a dopant and covers at least a portion of the dielectric layer.
[0003] Patent document 1 proposes a method for manufacturing a solid electrolytic capacitor, which comprises a step of forming a preliminary conductive layer when forming a conductive polymer layer on a valve action metal having a dielectric oxide film formed thereon, and a step of forming a conductive polymer layer on the preliminary conductive layer by electrolytic polymerization using an electrolytic polymerization solution for forming a conductive polymer. In the electrolytic polymerization solution for forming a conductive polymer, a polymerizable monomer and a compound represented by a specific formula as a supporting electrolyte are dissolved in a solvent.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2014-175424 Summary of the invention
[0007] Problems to be solved by the invention
[0008] Solid electrolytic capacitors are sometimes exposed to high temperature environments. Therefore, high thermal stability is required for solid electrolytic capacitors and solid electrolytic capacitor elements.
[0009] Means for solving problems
[0010] A first aspect of the present invention relates to a solid electrolytic capacitor element comprising an anode body, a dielectric layer formed on a surface of the anode body, and a cathode portion covering at least a portion of the dielectric layer.
[0011] The cathode portion includes a solid electrolyte layer covering at least a portion of the dielectric layer.
[0012] Based on thermogravimetric analysis, the solid electrolyte constituting the above-mentioned solid electrolyte layer is heated to 180°C, maintained at 180°C for 20 minutes, cooled from 180°C to 30°C, and then heated from 30°C to 260°C at a rate of 20°C / min. The weight reduction rate is less than 3%.
[0013] A second aspect of the present invention relates to a solid electrolytic capacitor element comprising an anode body, a dielectric layer formed on a surface of the anode body, and a cathode portion covering at least a portion of the dielectric layer.
[0014] The cathode portion includes a solid electrolyte layer covering at least a portion of the dielectric layer.
[0015] The solid electrolyte layer comprises a conductive polymer and a dopant component.
[0016] The dopant component comprises an aromatic compound having an electron-withdrawing functional group and an electron-donating functional group on an aromatic ring.
[0017] The aromatic compound has at least a first functional group: a sulfonic group and a second functional group: a carboxyl group as the electron-withdrawing functional group, and has at least one selected from a third functional group: a hydroxyl group and an alkoxy group as the electron-donating functional group.
[0018] In one molecule of the aromatic compound, when the number of the first functional group is n1, the number of the second functional group is n2, and the number of the third functional group is n3, n1≥1, n2≥1, n3≥1, and (n1+n2+n3)≥4.
[0019] A third aspect of the present invention relates to a solid electrolytic capacitor including at least one of the above-mentioned solid electrolytic capacitor elements.
[0020] Effects of the Invention
[0021] A solid electrolytic capacitor element having excellent thermal stability and a solid electrolytic capacitor including the solid electrolytic capacitor element can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a schematic cross-sectional view of a solid electrolytic capacitor according to one embodiment of the present invention. DETAILED DESCRIPTION
[0023] The novel features of the present invention are described in the appended claims, but both the configuration and content of the present invention together with other objects and features of the present invention can be better understood through the following detailed description with reference to the accompanying drawings.
[0024] In a solid electrolytic capacitor, if air invades the interior, the action of moisture or oxygen contained in the air causes the decomposition of the dopant component or the oxidation degradation of the conductive polymer, and the conductivity of the solid electrolyte layer is sometimes reduced. The reduction in the conductivity of the solid electrolyte layer leads to a reduction in the performance of the solid electrolytic capacitor, such as an increase in the equivalent series resistance (ESR) of the solid electrolytic capacitor or a decrease in the electrostatic capacitance. The decomposition of the dopant component and the oxidation degradation of the conductive polymer are particularly significant in a high temperature environment. Solid electrolytic capacitors are sometimes used in a high temperature environment depending on their use. In addition, solid electrolytic capacitors are generally soldered to the substrate after being exposed to a high temperature reflow process. If the dopant component is easy to decompose, a large amount of gas is generated in the reflow process, the airtightness is reduced, and the reliability of the solid electrolytic capacitor is reduced. Therefore, it is required that the decomposition of the dopant component and the oxidation degradation of the conductive polymer are suppressed even in a high temperature environment and have excellent thermal stability.
[0025] In view of the above, in the solid electrolytic capacitor element of the first aspect of the present invention, based on thermogravimetric analysis, the weight loss rate of the solid electrolyte constituting the solid electrolyte layer when heated to 180°C, maintained at 180°C for 20 minutes, cooled from 180°C to 30°C, and then heated from 30°C to 260°C at a rate of 20°C / min is less than 3%.
[0026] According to the first aspect of the present invention, by reducing the weight reduction rate of the above-mentioned solid electrolyte to less than 3%, the generation of gas under heating conditions such as the reflow soldering process is suppressed. Therefore, the reduction in the airtightness of the solid electrolytic capacitor in the reflow soldering process is suppressed. Even if exposed to a high temperature environment, gas generation is suppressed and high airtightness is ensured, so that the variation in capacitor performance can be suppressed to a low level. In addition, in the solid electrolytic capacitor element and the solid electrolytic capacitor, the degradation of the solid electrolyte is suppressed even if exposed to a high temperature environment, so that the reduction in electrostatic capacitance or the increase in ESR can be reduced. Therefore, high thermal stability of the solid electrolytic capacitor element and the solid electrolytic capacitor can be obtained, and high reliability can be ensured. According to the present invention, the above-mentioned weight reduction rate can also be suppressed to less than 2.5% or less than 2%, and can also be suppressed to less than 1% or less than 0.8% (or less than 0.5%).
[0027] In the solid electrolytic capacitor element of the first aspect, a dopant component of an aromatic compound containing an electron-withdrawing functional group and an electron-donating functional group as required in an aromatic ring may also be used in the solid electrolyte layer. Here, in the aromatic compound, when the number of electron-withdrawing functional groups is m1 and the number of electron-donating functional groups is m2 in one molecule of the aromatic compound, (m1-m2)≥2. Such an aromatic compound is sometimes referred to as a dopant IA.
[0028] For dopants, when there are more than two electron-withdrawing functional groups in the aromatic ring, it is easy to coordinate firmly with the conductive polymer, and there is a trend that dedoping can be suppressed even in a high temperature environment, so it is easy to ensure the high conductivity of the solid electrolyte layer. On the other hand, the electron-donating functional group has the effect of capturing oxygen free radicals. In the case where the dopant has an electron-donating functional group, in the dopant in the state of being coordinated to the conductive polymer by the effect of the electron-withdrawing functional group, the electron-donating functional group can be present in the vicinity of the conductive polymer. Through the electron-donating functional group, it is possible to capture oxygen free radicals in the vicinity of the conductive polymer, so even in a high temperature environment, the oxidative degradation of the conductive polymer can be effectively reduced. However, if the electron density of the aromatic ring, especially the electron density in the carbon atom replaced by the electron-withdrawing functional group, becomes high, the electron-withdrawing functional group is easy to electrophilically replace the carbon atom, and the electron-withdrawing functional group is separated, so there is a trend that dedoping is easy to carry out. When the dopant IA is used, the number of electron-withdrawing functional groups m1 and the number of electron-donating functional groups m2 satisfy (m1-m2)≥2, so even when the dopant IA has electron-donating functional groups, an excellent dedoping suppression effect can be obtained, and even if the solid electrolytic capacitor element is exposed to a high temperature environment, the decrease in electrostatic capacitance or the increase in ESR can be reduced. Therefore, high thermal stability and high reliability of the solid electrolytic capacitor element and the solid electrolytic capacitor can be ensured.
[0029] In the solid electrolytic capacitor element of the second aspect of the present invention, a dopant component containing an aromatic compound is used in the solid electrolyte layer, wherein the aromatic compound has a first functional group: a sulfonic group, a second functional group: a carboxyl group, and a third functional group: at least one selected from a hydroxyl group and an alkoxy group in an aromatic ring. Here, the aromatic compound satisfies n1≥1, n2≥1, n3≥1, and (n1+n2+n3)≥4 in one molecule of the aromatic compound when the number of the first functional group is n1, the number of the second functional group is n2, and the number of the third functional group is n3. Such an aromatic compound is sometimes referred to as a dopant IB.
[0030] In this specification, dopant IA and dopant IB are sometimes collectively referred to as the first dopant. In addition, at least one selected from dopant IA and dopant IB is sometimes referred to as the first dopant. In the first aspect, the first dopant is at least dopant IA, and in the second aspect, the first dopant is at least dopant IB.
[0031] According to the second aspect of the present invention, the dopant IB is a compound having an electron-withdrawing first functional group and a second functional group on an aromatic ring (benzene ring, naphthalene ring, etc.), which makes it easy to coordinate firmly with the conductive polymer, and suppresses dedoping even in a high temperature environment, so it is easy to ensure the high conductivity of the solid electrolyte layer. In addition, the dopant IB has excellent hydrolysis resistance due to such a structure, and decomposition in a high temperature environment is suppressed. Therefore, the dopant IB shows high thermal stability. In the dopant IB, the total number of the first to third functional groups (=n1+n2+n3) is 4 or more. That is, the number of at least any one of the first to third functional groups is 2 or more. When the number of at least any one of the first functional group and the second functional group is 2 or more, it is easy to ensure the higher thermal stability of the dopant IB. In addition, the dopant IB has an electron-donating third functional group in addition to the first functional group and the second functional group. The third functional group has the function of capturing oxygen free radicals. In the dopant IB in the state of being coordinated to the conductive polymer by the action of the first functional group and the second functional group, the third functional group can be present near the conductive polymer. Through the third functional group, oxygen free radicals can be captured near the conductive polymer, so even in a high temperature environment, the oxidative degradation of the conductive polymer can be effectively reduced. When the number of the third functional group is more than 2, the capture effect of oxygen free radicals is improved, thereby further improving the effect of reducing the oxidative degradation of the conductive polymer. In this way, in the present invention, by using a dopant component containing dopant IB, the decomposition of the dopant component and the oxidative degradation of the conductive polymer under a high temperature environment are reduced. Therefore, the excellent thermal stability of the solid electrolytic capacitor element and the solid electrolytic capacitor can be ensured. In addition, by making the dopant IB have excellent hydrolysis resistance, the solid electrolyte layer is not easily affected by moisture even in a high temperature environment. Thus, the moisture resistance characteristics of the solid electrolytic capacitor element and the solid electrolytic capacitor can also be improved.
[0032] In addition, according to the second aspect of the present invention, the decomposition of the dopant component is suppressed, so the amount of gas generated in the reflow process can be reduced. The solid electrolyte layer contained in such a solid electrolytic capacitor has a small weight reduction rate under heating conditions equivalent to the reflow process. For example, based on thermogravimetric analysis, the solid electrolyte constituting the solid electrolyte layer is heated to 180°C, kept at 180°C for 20 minutes, cooled from 180°C to 30°C, and then heated from 30°C to 260°C at a rate of 20°C / min. The weight reduction rate is less than 3%. In this way, according to the present invention, the generation of gas under heating conditions equivalent to the reflow process is suppressed, so the reduction in the airtightness of the solid electrolytic capacitor in the reflow process is suppressed. Even if exposed to a high temperature environment, gas generation is suppressed to ensure high airtightness, and oxidation degradation of the conductive polymer is suppressed, so the reduction in electrostatic capacitance or the increase in ESR can be reduced. Therefore, the high reliability of the solid electrolytic capacitor element and the solid electrolytic capacitor can be ensured. According to the present invention, the weight reduction rate can be suppressed to 2.5% or less, or 2% or less, and can also be suppressed to less than 1% or 0.8% or less (or 0.5% or less). Therefore, the excellent reliability of the solid electrolytic capacitor can be ensured.
[0033] It should be noted that the weight reduction rate of the solid electrolyte can be determined by thermogravimetric analysis according to the following steps. First, take out the solid electrolytic capacitor element from the solid electrolytic capacitor, and prepare a sample of the solid electrolyte by cutting part of the solid electrolyte layer. The sample is placed in a thermogravimetric analyzer, heated from room temperature (temperature above 20°C and below 35°C) to 180°C, kept at 180°C for 20 minutes, cooled from 180°C to 30°C, and the weight w0 of the cooled sample is measured. Next, the sample is heated from 30°C to 260°C at a rate of 20°C / min using a thermogravimetric analyzer, and the weight w1 of the heated sample is measured. The weight reduction Δw (=w0-w1) of the sample when the temperature is increased from 30°C to 260°C is determined, and the ratio (%) of Δw when w0 is set to 100% is calculated as the weight reduction rate of the solid electrolyte layer. All these thermogravimetric analyses were performed under the circulation of nitrogen. As a thermogravimetric analyzer, for example, a differential thermal and thermogravimetric simultaneous measurement apparatus (NEXTA STA300) manufactured by Hitachi High-Tech Science Corporation can be used.
[0034] Hereinafter, the solid electrolytic capacitor and the solid electrolytic capacitor element (hereinafter, sometimes simply referred to as a capacitor element) of the present invention will be described in more detail with reference to the drawings as needed.
[0035] [Solid electrolytic capacitors]
[0036] The solid electrolytic capacitor has one or more capacitor elements. In at least one of the capacitor elements included in the solid electrolytic capacitor, the solid electrolyte layer may contain the first dopant. Preferably, the solid electrolyte layer contains the first dopant in more than 50% of the number of capacitor elements included in the solid electrolytic capacitor, more preferably, the solid electrolyte layer contains the first dopant in more than 75%, and further preferably, the solid electrolyte layer contains the first dopant in all the capacitor elements.
[0037] (Capacitor Components)
[0038] (Anode)
[0039] The anode body may contain a valve metal, an alloy containing a valve metal, a compound containing a valve metal, and the like. These materials may be used alone or in combination of two or more. As the valve metal, it is preferred to use, for example, aluminum, tantalum, niobium, and titanium. The anode body having a porous surface is obtained by roughening the surface of a substrate (foil-like or plate-like substrate, etc.) containing a valve metal, for example, by etching. Roughening may be performed by, for example, etching treatment. In addition, the anode body may also be a formed body of particles containing a valve metal or a sintered body thereof. It should be noted that the sintered body has a porous structure.
[0040] (Dielectric layer)
[0041] The dielectric layer is an insulating layer that functions as a dielectric and is formed in a manner that covers at least a portion of the surface of the anode body. The dielectric layer is formed by anodizing the valve action metal on the surface of the anode body by chemical conversion treatment or the like. The dielectric layer only needs to be formed to cover at least a portion of the anode body. The dielectric layer is usually formed on the surface of the anode body. The dielectric layer is formed on the porous surface of the anode body, and therefore extends along the inner wall surface of the pores and pits on the surface of the anode body.
[0042] The dielectric layer includes an oxide of a valve metal. For example, when tantalum is used as the valve metal, the dielectric layer includes Ta2O5, and when aluminum is used as the valve metal, the dielectric layer includes Al2O3. It should be noted that the dielectric layer is not limited to this, as long as it is a layer that functions as a dielectric.
[0043] (Cathode)
[0044] The cathode portion at least includes a solid electrolyte layer covering at least a portion of the dielectric layer. The cathode portion is usually formed on the surface of at least a portion of the anode body through the dielectric layer. The cathode portion may include a solid electrolyte layer and a cathode lead layer covering at least a portion of the solid electrolyte layer. The solid electrolyte layer and the cathode lead layer are described below.
[0045] (Solid Electrolyte Layer)
[0046] The solid electrolyte layer is formed on the surface of the anode body through the dielectric layer to cover the dielectric layer. The solid electrolyte layer does not necessarily need to cover the entire dielectric layer (the entire surface), as long as it is formed in a manner that covers at least a portion of the dielectric layer. The solid electrolyte layer constitutes at least a portion of the cathode portion in the solid electrolytic capacitor.
[0047] The solid electrolyte layer contains a conductive polymer and a dopant component.
[0048] (Conductive polymer)
[0049] As the conductive polymer, known conductive polymers used in solid electrolytic capacitors can be used, for example, π-conjugated conductive polymers, etc. As conductive polymers, for example, polymers with basic skeletons such as polypyrrole, polythiophene, polyaniline, polyfuran, polyacetylene, polyphenylene (Japanese: ポリフエニレン), polyphenylene vinylene (Japanese: ポリフエニレンビレン), polybenzone and polythiophene vinylene (Japanese: ポリチオフエンビレン) can be cited. Among them, polymers with polypyrrole, polythiophene or polyaniline as basic skeletons are preferred. The above-mentioned polymers also include homopolymers, copolymers of two or more monomers, and their derivatives (substitutes with substituents, etc.). For example, polythiophene includes poly (3,4-ethylenedioxythiophene) and the like.
[0050] The conductive polymer may be used alone or in combination of two or more.
[0051] The weight average molecular weight (Mw) of the conductive polymer is not particularly limited, but is, for example, 1,000 or more and 1,000,000 or less.
[0052] In this specification, the weight average molecular weight (Mw) is a value in terms of polystyrene measured by gel permeation chromatography (GPC). In general, GPC is measured using a polystyrene gel column and water / methanol (volume ratio 8 / 2) as a mobile phase.
[0053] (Dopant ingredient)
[0054] The dopant component only needs to include at least the first dopant, and may further include a second dopant other than the first dopant as needed. The ratio of the first dopant in the dopant component is, for example, more than 50 mass%, more than 75 mass%, more than 90 mass%, or more than 95 mass%. The ratio of the first dopant in the dopant component is less than 100 mass%. The dopant component may also be composed of only the first dopant. In addition, the ratio of dopant IA in the dopant component may also be set to the above range. The ratio of dopant IB in the dopant component may also be set to the above range. In the first aspect, the dopant component may be composed of only dopant IA. In the second aspect, the dopant component may be composed of only dopant IB.
[0055] (First dopant)
[0056] As the aromatic ring possessed by the first dopant, a benzene ring, a naphthalene ring, an anthracene ring, a phenanthrene ring, etc. can be cited. The number of carbon atoms in the aromatic ring is, for example, 6 or more and 20 or less, 6 or more and 14 or less, or 6 or more and 10 or less. In the case of a benzene ring or a naphthalene ring, the molecular size is small, the molecule of the first dopant is easy to approach the conductive polymer, and the positions of multiple electron-withdrawing functional groups are also easy to become closer. Therefore, it is easy to be firmly coordinated to the conductive polymer, and it is easy to further ensure the high conductivity of the solid electrolyte layer.
[0057] The first dopant has a plurality of functional groups on the aromatic ring. The plurality of functional groups at least include an electron-withdrawing functional group. The plurality of functional groups may also include an electron-donating functional group. The first dopant has two or more electron-withdrawing functional groups in one molecule.
[0058] Examples of the electron-withdrawing functional group include a sulfo group, a carboxyl group, a nitro group, a cyano group, an aldehyde group, an acyl group, a tosyl group (Japanese: tosyl group), and a halogen atom (a fluorine group, a chlorine group, a bromine group, an iodine group, etc.). From the viewpoint of obtaining higher capacitor performance, among the electron-withdrawing functional groups, a sulfo group (the first functional group) and a carboxyl group (the second functional group) are preferred.
[0059] As the electron-donating functional group (the third functional group), a hydroxyl group and an alkoxy group are preferred. When the first dopant has a plurality of third functional groups, each third functional group may be any one of a hydroxyl group and an alkoxy group. The number of carbon atoms of the alkoxy group is, for example, 1 to 10, and may be 1 to 6. From the viewpoint of easily obtaining a higher oxygen radical capture effect, each third functional group is preferably a hydroxyl group or an alkoxy group having 1 to 4 carbon atoms. The alkoxy group may be either a straight chain or a branched chain. Specific examples of the alkoxy group include a methoxy group, an ethoxy group, a n-propoxy group, an isopropoxy group, a n-butoxy group, an isobutoxy group, a sec-butoxy group, a tert-butoxy group, a hexyloxy group, a 2-ethylhexyloxy group, and an octyloxy group, but are not limited to these.
[0060] It should be noted that in the solid electrolyte layer, the free form (-SO3H), the anion form (-SO3 - ), or a salt form, or may contain a sulfonic group as the first functional group in a form that is bonded to or interacts with a conductive polymer. In this specification, sometimes all of these sulfonic groups are included and are simply referred to as "sulfonic groups". Similarly, in the solid electrolyte layer, the sulfonic group may be in a free form (-COOH), an anionic form (-COO - ), or a salt form, or may contain a carboxyl group in a form that is bonded to or interacts with a conductive polymer. In this specification, sometimes all of these forms of carboxyl groups are included and are simply referred to as "carboxyl groups". In addition, the carboxyl group may be in a free form (-OH), an anionic form (-O - ), or the form of a salt contains a hydroxyl group of the third functional group (in other words, a phenolic hydroxyl group). It should be noted that the salt may be a salt of a sulfonate anion or a carboxylate anion with any of an organic base (organic amine, organic ammonium, etc.) and an inorganic base (metal hydroxide, ammonia, etc.).
[0061] When the first dopant has two or more first functional groups, at least a part of the first functional groups may be contained in the same form, or all of the first functional groups may be contained in different forms. When the first dopant has two or more second functional groups, at least a part of the two or more second functional groups may be contained in the same form, or all of them may be contained in different forms. When the first dopant has two or more third functional groups, at least a part of the two or more third functional groups may be contained in the same form, or all of them may be contained in different forms.
[0062] In the dopant IA, the number m1 of electron-withdrawing functional groups in one molecule is m1≥2, m1≥3, or m1≥4. The upper limit of the number m1 can be determined according to the number of carbon atoms in the aromatic ring. The number m1 can be m1≤6, or m1≤4. These upper and lower limits can be arbitrarily combined.
[0063] In the first dopant (specifically, dopant IA or dopant IB), the number n1 of the first functional group is, for example, n1≥1, or n1≥2. The number n2 of the second functional group is, for example, n2≥1, or n2≥2. When at least one of n1≥2 and n2≥2 is satisfied, the thermal stability of the first dopant can be further improved. In the case of n1≥2, a higher binding force of the first dopant to the conductive polymer can be obtained, so dedoping is suppressed even in a high temperature environment, which is more advantageous in ensuring the high conductivity of the solid electrolyte layer. In the case of n2≥2, the hydrolysis resistance of the first dopant can be further improved, and the effect of suppressing the decomposition of the first dopant is further improved even in a high temperature environment. Therefore, it is advantageous in further improving the thermal stability of the solid electrolyte layer.
[0064] In the dopant IA, the number m2 of electron-donating functional groups (or the number n3 of the third functional groups) in one molecule is determined according to the number m1 of electron-withdrawing functional groups within the range satisfying (m1-m2)≥2. The number m2 (or n3) may be m2 (or n3)≤1. When the type and number of electron-withdrawing functional groups are the same, when the number m2 of electron-donating functional groups (or the number n3 of the third functional groups) is 1 or more, there is a tendency for the weight reduction rate to become lower compared to the case where the number m2 (or n3) is 0. From the viewpoint of further reducing the weight reduction rate, the dopant IA preferably has electron-donating functional groups (m2 (or n3)≥1), and may be m2 (or n3)=1.
[0065] The dopant IB has the first to third functional groups in an aromatic ring (e.g., a benzene ring, a naphthalene ring, or the like) such that the number of functional groups n1, n2, and n3 satisfies the range of n1≥1, n2≥1, n3≥1, and (n1+n2+n3)≥4. In the dopant IB, the upper limit of (n1+n2+n3) can be determined based on the number of carbon atoms in the aromatic ring. For example, when the aromatic ring is a benzene ring, (n1+n2+n3)≤6, and when the aromatic ring is a naphthalene ring, (n1+n2+n3)≤8. It is also possible that (n1+n2+n3)≤6 is acceptable regardless of the type of the aromatic ring.
[0066] In the dopant IB, the number n3 of the third functional group satisfies n3 ≥ 1, and may be n3 ≥ 2. In the case of n3 ≥ 2, the effect of capturing oxygen radicals is further enhanced, which is more advantageous from the viewpoint of suppressing oxidative degradation of the conductive polymer.
[0067] When the first dopant has a first functional group, the position of the first functional group in the aromatic ring is not particularly limited. When the first dopant has a naphthalene ring as the aromatic ring, it is preferred that the first functional group is present at at least one of the 2nd, 3rd, 6th and 7th positions of the naphthalene ring. In this case, the first dopant is more accessible to the conductive polymer, which is advantageous in improving the conductivity of the solid electrolyte layer.
[0068] In the first dopant, the positions of the first functional group and the second functional group in the aromatic ring (benzene ring, naphthalene ring, etc.) are not particularly limited. In the case where the first dopant has a benzene ring as the aromatic ring, the position of the second functional group in the benzene ring can be any one of the ortho position, meta position and para position relative to the first functional group. In the benzene ring, when the second functional group is located at the meta position relative to the first functional group, it is preferred from the perspective of easily obtaining a higher hydrolysis resistance of the first dopant. In the case where the first dopant has more than two first functional groups, it is preferred that the second functional group is located at the meta position relative to at least one first functional group. In the case where the first dopant has more than two second functional groups, it is preferred that at least one second functional group is located at the meta position relative to the first functional group.
[0069] In the case where the first dopant has a first functional group and an electron-donating functional group (or a third functional group), the position of the electron-donating functional group (or the third functional group) in the aromatic ring (benzene ring, naphthalene ring, etc.) is not particularly limited. In the case where the first dopant has a benzene ring as an aromatic ring, the position of the electron-donating functional group (or the third functional group) in the benzene ring can be any one of the ortho position, meta position, and para position relative to the first functional group. It is believed that when the position of the electron-donating functional group (or the third functional group) is ortho or meta position relative to the first functional group, it is easy to capture oxygen free radicals near the conductive polymer, thereby further improving the effect of suppressing oxidative degradation of the conductive polymer. The position of the electron-donating functional group (or the third functional group) can be ortho or para position relative to the first functional group. In this case, in addition to being easy to introduce each functional group into the benzene ring, it is also easy to achieve a balance between the high hydrolysis resistance brought by the electron-withdrawing functional group (the first functional group and the second functional group) and the high oxygen radical capture effect brought by the electron-donating functional group (or the third functional group). Therefore, it is advantageous in further improving the thermal stability of the solid electrolyte layer.
[0070] As the first dopant having a naphthalene ring as an aromatic ring, at least one selected from an aromatic compound having the number m1 of electron-withdrawing functional groups of m1≥4, an aromatic compound having the number n1 of sulfonic groups of n1≥2 and the number n2 of carboxyl groups of n2=0, and a dopant IB (an aromatic compound having the number m2 (or n3) of electron-donating functional groups of m2≥1, etc.) can be used. These compounds are easy to obtain a lower weight reduction rate. From the same point of view, as a dopant IA having a naphthalene ring as an aromatic ring, a dopant IA other than 6,8-disulfo-2-naphthoic acid, 5,7-disulfo-2-naphthoic acid, 3,6-disulfo-1-naphthoic acid, 4,8-disulfo-2-naphthoic acid and 3,7-disulfo-2-naphthoic acid can be used. It should be noted that these disulfonaphthoic acids do not have substituents other than two sulfonic groups and one carboxyl group.
[0071] The first dopant may have a first substituent other than the electron-withdrawing functional group and the electron-donating functional group (for example, the first to third functional groups) as needed. In addition, the first dopant may be a compound having a non-aromatic ring Z fused to an aromatic ring (benzene ring, naphthalene ring, etc.). In the first dopant having such a structure, two carbon atoms that are not substituted by the electron-withdrawing functional group and the electron-donating functional group (the first to third functional groups, etc.) among the carbon atoms constituting the aromatic ring (for example, the carbon atoms at positions 1 to 6 of the benzene ring) are linked by an aliphatic chain. The aliphatic chain may be saturated or unsaturated. The first dopant may have one or more second substituents on the aliphatic chain. In addition to electron-withdrawing functional groups and electron-donating functional groups (first to third functional groups, etc.), compounds having such a first substituent on an aromatic ring (benzene ring, naphthalene ring, etc.) and compounds condensed with a ring Z that may have a second substituent are also included in the first dopant (or dopant IA or dopant IB).
[0072] As the first substituent that the first dopant may have on the aromatic ring (benzene ring, naphthalene ring, etc.), a hydrocarbon group may be mentioned, for example. In the dopant IB, the first substituent may be an electron-donating group other than the third functional group, an electron-withdrawing group other than the first functional group and the second functional group, etc. From the viewpoint of being easy to bring into play the effects brought by the first to third functional groups in a good balance, a hydrocarbon group is preferred. The hydrocarbon group may be any of aliphatic, alicyclic and aromatic. From the viewpoint of being easy to coordinate to the conductive polymer, the hydrocarbon group is preferably an aliphatic hydrocarbon group. The number of carbon atoms of the aliphatic hydrocarbon group is, for example, 1 to 10, or 1 to 6 or 1 to 4. The aliphatic hydrocarbon group may be any of saturated or unsaturated. As the aliphatic hydrocarbon group, an alkyl, an alkenyl, a diene group, etc. may be mentioned.
[0073] The number n4 of the first substituent can be determined based on the number of carbon atoms in the aromatic ring, the number of electron-withdrawing functional groups, and the number of electron-donating functional groups. The number n4 of the first substituent is, for example, greater than or equal to 0 and less than or equal to 6, and may be greater than or equal to 0 and less than or equal to 4. In the case where the first dopant has a benzene ring as an aromatic ring, the number n4 of the first substituent is 0, 1, or 2. In the case where the first dopant has two or more first substituents, at least two first substituents may be the same or all different. From the viewpoint of being able to easily and well-balance the effects of the electron-withdrawing functional group and the electron-donating functional group (for example, the first to third functional groups), it is also preferred that the first dopant does not have a first substituent.
[0074] When the first dopant includes ring Z, as the second substituent that the first dopant may have on the aliphatic chain constituting ring Z, there may be mentioned the groups described for the electron-withdrawing functional group, the groups described for the first to third functional groups, and the groups described for the first substituent. The number n5 of the second substituents in the first dopant may be 1 or may be 2 or more. When the first dopant has two or more second substituents, some of the second substituents may be the same, or all of the second substituents may be different.
[0075] From the viewpoint of making it easy to bring the first dopant close to the conductive polymer, the first dopant preferably does not have the non-aromatic ring Z as described above.
[0076] The dopant component may include one first dopant or two or more first dopants. The dopant component may include one dopant IA or two or more dopant IA. The dopant component may include one dopant IB or two or more dopant IB. The dopant component may include at least one dopant IB and at least one of the dopants IA not included in the dopant IB.
[0077] (Second dopant)
[0078] The second dopant may be any dopant other than the first dopant, and examples thereof include at least one selected from anions and polyanions.
[0079] Examples of the anion include, but are not particularly limited to, sulfate ions, nitrate ions, phosphate ions, borate ions, organic sulfonate ions, and carboxylate ions. Examples of the dopant that generates sulfonate ions include p-toluenesulfonic acid and naphthalenesulfonic acid.
[0080] Examples of the polyanion include polymeric polysulfonic acid and polymeric polycarboxylic acid. Examples of the polymeric polysulfonic acid include polyvinylsulfonic acid, polystyrenesulfonic acid, polyallylsulfonic acid, polyacryloylsulfonic acid, and polymethacryloylsulfonic acid. Examples of the polymeric polycarboxylic acid include polyacrylic acid and polymethacrylic acid. Polyanions also include polyester sulfonic acid and phenolsulfonic acid phenolic resin. However, the polyanion is not limited thereto.
[0081] The anions and the polyanions may be contained in the solid electrolyte layer in the form of salts. In the solid electrolyte layer, the anions and the polyanions may be bonded to or interacted with the conductive polymers, thereby forming a conductive polymer complex together with the conductive polymers.
[0082] The dopant component may contain one type of the second dopant, or may contain two or more types of the second dopant.
[0083] In the solid electrolytic capacitor element of the present invention, as described above, the weight reduction rate of the solid electrolyte based on thermogravimetric analysis can be suppressed to a low level. The weight reduction rate of the solid electrolyte can be adjusted, for example, based on the type of dopant, the ratio of the dopant to the conductive polymer, the polymerization conditions when forming the conductive polymer (for example, the polymerization potential of the electrolytic polymerization, the concentration of the conductive polymer precursor in the treatment solution for polymerization, and the concentration of the dopant), etc.
[0084] (other)
[0085] The amount of the dopant component contained in the solid electrolyte layer is, for example, 10 to 1000 parts by mass, or 20 to 500 parts by mass or 50 to 200 parts by mass relative to 100 parts by mass of the conductive polymer.
[0086] The solid electrolyte layer may be a single layer or may be composed of multiple layers. When the solid electrolyte layer is composed of multiple layers, the conductive polymer contained in each layer may be the same or different. In addition, the composition of the dopant component contained in each layer may be the same or different. When the solid electrolyte layer is composed of multiple layers, at least one layer may contain the first dopant.
[0087] The solid electrolyte layer may further contain known additives and known conductive materials other than the conductive polymer as necessary. Examples of such conductive materials include at least one selected from conductive inorganic materials such as manganese dioxide and TCNQ complex salts.
[0088] In addition, a layer for improving adhesion may be interposed between the dielectric layer and the solid electrolyte layer.
[0089] The solid electrolyte layer is formed, for example, by using a treatment solution containing a precursor of a conductive polymer and a dopant component to polymerize the precursor on the dielectric layer. The polymerization can be carried out by at least one of chemical polymerization and electrolytic polymerization. As a precursor of the conductive polymer, at least one selected from monomers, oligomers and prepolymers can be cited. Each of the oligomers and prepolymers has a structure formed by, for example, multiple monomer units connected together. One precursor can be used, or two or more can be used in combination. The solid electrolyte layer can be formed by attaching a treatment solution (for example, a dispersion or a solution) containing a conductive polymer and a dopant component to the dielectric layer and then drying it. As a dispersion medium (or solvent), for example, water, an organic solvent or a mixture thereof can be cited. The treatment solution may further contain other components such as additives.
[0090] When using a treatment liquid containing a precursor of a conductive polymer and a dopant component, an oxidant is used as necessary to polymerize the precursor. The first dopant can be used as the oxidant, but an oxidant other than the first dopant can also be used. The oxidant can be contained in the treatment liquid as an additive. In addition, the oxidant can be applied to the anode body before or after the treatment liquid is brought into contact with the anode body formed with a dielectric layer. As such an oxidant, sulfates, sulfonic acids or their salts can be exemplified. The oxidant can be used alone or in combination of two or more. As sulfates, for example, salts of sulfuric acid such as iron sulfate and sodium persulfate, and salts of sulfuric acid such as persulfate and metals can be cited. As metals constituting the salts, for example, alkali metals (sodium, potassium, etc.), iron, copper, chromium, zinc, etc. can be cited. In addition to the function of an oxidant, sulfonic acid or its salt has a function as a dopant. As sulfonic acid or its salt, the low molecular weight sulfonic acid or its salt exemplified for the second dopant can be used. As an oxidant, a sulfonic acid that can generate Fe 3+ Compounds (ferric sulfate, etc.), persulfates (sodium persulfate, ammonium persulfate, etc.), hydrogen peroxide, etc. The oxidizing agent may be used alone or in combination of two or more.
[0091] The process of forming a solid electrolyte layer by immersion in a treatment solution and polymerization (or drying) can be performed once or repeated multiple times. In each case, the composition and viscosity of the treatment solution can be the same, or at least one of the conditions can be changed.
[0092] From the viewpoint of easy control of the properties of the solid electrolyte, it is preferred to form the solid electrolyte layer by electrolytic polymerization. Electrolytic polymerization can be performed by applying a polymerization voltage in a state where the anode body having a dielectric layer is in contact with (e.g., immersed in) a treatment solution containing a precursor of a conductive polymer and a dopant component. The application of the polymerization voltage can be performed via a power supply.
[0093] In electrolytic polymerization, the polymerization voltage is, for example, 1 V or more and 3.5 V or less (or 3 V or less), and may be 2 V or more and 3.5 V or less (or 3 V or less). It should be noted that the polymerization voltage is the voltage of the current source relative to the reference electrode (silver / silver chloride electrode (Ag / Ag + ))'s potential.
[0094] In the treatment liquid, the ratio of the dopant component to the conductive polymer precursor is, for example, 0.1 mol to 0.75 mol, or 0.4 mol to 0.75 mol, per 1 mol of the conductive polymer monomer unit.
[0095] The temperature for performing the electrolytic polymerization is, for example, 5° C. to 60° C., or 15° C. to 35° C.
[0096] (Cathode extraction layer)
[0097] The cathode lead layer only needs to have at least a first layer that contacts the solid electrolyte layer and covers at least a portion of the solid electrolyte layer, and may also have a first layer and a second layer that covers the first layer. As the first layer, for example, a layer containing conductive particles, a metal foil, etc. can be cited. As the conductive particles, for example, at least one selected from conductive carbon and metal powder can be cited. For example, the cathode lead layer can be composed of a layer containing conductive carbon as the first layer and a layer containing metal powder or a metal foil as the second layer. In the case of using a metal foil as the first layer, the cathode lead layer can also be composed of the metal foil.
[0098] The first layer containing conductive carbon can be formed, for example, by immersing an anode body having a dielectric layer formed with a solid electrolyte layer in a dispersion containing conductive carbon, or by applying a paste containing conductive carbon to the surface of the solid electrolyte layer. As conductive carbon, graphites such as artificial graphite and natural graphite can be used. As the dispersion and the paste, a mixture in which conductive carbon is dispersed in an aqueous liquid medium can be used.
[0099] The layer containing metal powder as the second layer can be formed, for example, by laminating a composition containing metal powder on the surface of the first layer. As such a second layer, for example, a metal paste layer formed using a composition containing metal powder such as silver particles and a resin (binder resin) can be used. As the resin, a thermoplastic resin can also be used, but a thermosetting resin such as an imide resin or an epoxy resin is preferably used.
[0100] When a metal foil is used as the first layer, the type of metal is not particularly limited, and preferably a valve metal such as aluminum, tantalum, niobium, or an alloy containing a valve metal is used. The surface of the metal foil may be roughened by etching, etc. as needed. A chemical conversion film may be provided on the surface of the metal foil, and a film of a metal (dissimilar metal) or a non-metallic film different from the metal constituting the metal foil may also be provided. Examples of the dissimilar metal and non-metal include metals such as titanium and non-metals such as carbon (conductive carbon, etc.).
[0101] The coating of the above-mentioned different metal or non-metal (for example, conductive carbon) may be used as the first layer, and the above-mentioned metal foil may be used as the second layer.
[0102] The thickness of each of the first layer and the second layer may be, for example, 0.1 μm or more and 100 μm or less, 0.5 μm or more and 50 μm or less, or 1 μm or more and 20 μm or less.
[0103] (Diaphragm)
[0104] When a metal foil is used for the cathode lead-out layer, a separator may be disposed between the metal foil and the anode body. The separator is not particularly limited, and nonwoven fabrics containing fibers of cellulose, polyethylene terephthalate, vinylon, polyamide (e.g., aliphatic polyamide, aromatic polyamide such as aramid) and the like may be used.
[0105] (other)
[0106] The solid electrolytic capacitor may be a wound type, a chip type, or a stacked type. The solid electrolytic capacitor may have two or more capacitor elements. For example, the solid electrolytic capacitor may have a stack of two or more capacitor elements. The solid electrolytic capacitor may also have two or more wound capacitor elements. The configuration of the capacitor element may be selected according to the type of the solid electrolytic capacitor.
[0107] In the capacitor element, one end of the cathode terminal is electrically connected to the cathode lead layer. The cathode terminal is coated with a conductive adhesive on the cathode lead layer, and is bonded to the cathode lead layer via the conductive adhesive. One end of the anode terminal is electrically connected to the anode body. The other end of the anode terminal and the other end of the cathode terminal are respectively led out from the resin outer casing or the shell. The other end of each terminal exposed from the resin outer casing or the shell is used for solder connection with a substrate on which a solid electrolytic capacitor is to be mounted.
[0108] The capacitor element is sealed with a resin outer casing or a housing. For example, the material resin of the capacitor element and the outer casing (for example, an uncured thermosetting resin and a filler) can be housed in a mold, and the capacitor element is sealed with a resin outer casing by transfer molding, compression molding, etc. At this time, the part of the other end side of the anode terminal connected to the anode lead drawn from the capacitor element and the part of the other end side of the cathode terminal are exposed from the mold respectively. In addition, a solid electrolytic capacitor can also be formed by housing the capacitor element in a bottomed housing so that the part of the other end side of the anode terminal and the cathode terminal is located on the opening side of the bottomed housing, and the opening of the bottomed housing is sealed with a sealant.
[0109] Figure 1 1 is a cross-sectional view schematically showing the structure of a solid electrolytic capacitor according to one embodiment of the present invention. Figure 1 As shown, the solid electrolytic capacitor 1 includes a capacitor element 2, a resin outer package 3 that seals the capacitor element 2, and an anode terminal 4 and a cathode terminal 5, at least a portion of which are exposed to the outside of the resin outer package 3. The anode terminal 4 and the cathode terminal 5 can be made of metal such as copper or a copper alloy. The resin outer package 3 has a substantially rectangular parallelepiped shape, and the solid electrolytic capacitor 1 also has a substantially rectangular parallelepiped shape.
[0110] The capacitor element 2 includes an anode body 6, a dielectric layer 7 covering the anode body 6, and a cathode body 8 covering the dielectric layer 7. The cathode body 8 includes a solid electrolyte layer 9 covering the dielectric layer 7 and a cathode lead layer 10 covering the solid electrolyte layer 9, constituting the above-mentioned cathode portion. In the example shown in the figure, the cathode lead layer 10 has a carbon layer 11 as a first layer and a metal paste layer 12 as a second layer. According to the present invention, the weight reduction rate of the solid electrolyte constituting the solid electrolyte layer 9 is 3% or less. Alternatively, the solid electrolyte layer 9 contains a conductive polymer and a dopant component containing a first dopant (dopant IB, etc.). With such a configuration, the capacitor element 2 and the solid electrolytic capacitor 1 show high thermal stability. In addition, the high reliability of the capacitor element 2 and the solid electrolytic capacitor 1 can be ensured.
[0111] The anode body 6 includes a region facing the cathode body 8 and a region not facing the cathode body 8. In the region of the anode body 6 not facing the cathode body 8, an insulating separation layer 13 is formed in a band-shaped manner covering the surface of the anode body 6 in a portion adjacent to the cathode body 8, thereby limiting the contact between the cathode body 8 and the anode body 6. In the region of the anode body 6 not facing the cathode body 8, another portion is electrically connected to the anode terminal 4 by welding. The cathode terminal 5 is electrically connected to the cathode body 8 via an adhesive layer 14 formed of a conductive adhesive.
[0112] The main surfaces 4S and 5S of the anode terminal 4 and the cathode terminal 5 are exposed from the same surface of the resin outer package 3. The exposed surfaces are used for solder connection with a substrate (not shown) on which the solid electrolytic capacitor 1 is to be mounted.
[0113] Example
[0114] Hereinafter, the present invention will be specifically described based on Examples and Comparative Examples, but the present invention is not limited to the following Examples.
[0115] 《Solid Electrolytic Capacitor A1》
[0116] Follow the steps below to make Figure 1 The solid electrolytic capacitor 1 (solid electrolytic capacitor A1) shown was used, and its characteristics were evaluated.
[0117] (1) Preparation of anode body 6
[0118] Anode body 6 was produced by roughening both surfaces of an aluminum foil (thickness: 100 μm) as a base material by etching.
[0119] (2) Formation of dielectric layer 7
[0120] The other end portion of anode body 6 was immersed in a chemical conversion solution, and a direct current voltage of 70 V was applied for 20 minutes to form dielectric layer 7 containing aluminum oxide.
[0121] (3) Formation of Solid Electrolyte Layer 9
[0122] An aqueous solution containing a pyrrole monomer and 4-hydroxy-5-sulfoisophthalic acid (dopant component) was prepared. The monomer concentration in the aqueous solution was 0.5 mol / L, and the concentration of 4-hydroxy-5-sulfoisophthalic acid was 0.3 mol / L. It should be noted that the 4-hydroxy-5-sulfoisophthalic acid used was represented by the following formula.
[0123] [Chemical formula 1]
[0124]
[0125] Anode body 6 and counter electrode having dielectric layer 7 formed in (2) were immersed in the obtained aqueous solution, and electrolytic polymerization was performed at 25° C. at a polymerization voltage of 3 V (polymerization potential relative to a silver reference electrode), thereby forming solid electrolyte layer 9 .
[0126] (4) Formation of cathode body 8
[0127] The anode body 6 having the solid electrolyte layer 9 obtained in (3) above is immersed in a dispersion in which graphite particles are dispersed in water, taken out of the dispersion, and then dried, thereby forming a carbon layer 11 at least on the surface of the solid electrolyte layer 9. Drying is performed at 130 to 180° C. for 10 to 30 minutes.
[0128] Next, a silver paste containing silver particles and a binder resin (epoxy resin) is applied to the surface of the carbon layer 11, and heated at 150 to 200° C. for 10 to 60 minutes to cure the binder resin to form the metal paste layer 12. In this way, the cathode body 8 composed of the carbon layer 11 and the metal paste layer 12 is formed.
[0129] Capacitor element 2 is produced in the above-described manner.
[0130] (5) Installation of solid electrolytic capacitor 1
[0131] Cathode body 8 of capacitor element 2 obtained in (4) is bonded to one end of cathode terminal 5 via conductive adhesive layer 14. One end of anode body 6 protruding from capacitor element 2 is bonded to one end of anode terminal 4 by laser welding.
[0132] Next, resin outer package 3 made of insulating resin is formed by molding around capacitor element 2 . At this time, the other end of anode terminal 4 and the other end of cathode terminal 5 are drawn out of resin outer package 3 .
[0133] In this way, the solid electrolytic capacitor A1 was completed. A total of 20 solid electrolytic capacitors A1 were produced in the same manner as above.
[0134] (6) Evaluation
[0135] The following evaluation was performed using a solid electrolytic capacitor.
[0136] (a) Change rate of ESR and change rate of electrostatic capacitance
[0137] In an environment of 20°C, using a 4-terminal LCR meter, the initial electrostatic capacitance (μF) of each solid electrolytic capacitor at a frequency of 120Hz was measured, and the initial ESR (mΩ) at a frequency of 100kHz was measured. Then, the average value (initial electrostatic capacitance: c0, initial ESR: r0) of the 20 solid electrolytic capacitors was calculated.
[0138] Next, the solid electrolytic capacitor was subjected to a reflow soldering treatment at 260°C for 3 minutes. After the reflow soldering treatment, the solid electrolytic capacitor was subjected to an accelerated test by applying the rated voltage to it for 500 hours at 145°C. Then, the capacitance and ESR were measured at 20°C using the same steps as the initial capacitance and ESR, and the average values of 20 solid electrolytic capacitors were obtained (capacitance after the accelerated test: c1, ESR after the accelerated test: r1). The change in capacitance caused by the accelerated test (=c1-c0) was obtained, and the ratio (%) of the change in capacitance when the initial average capacitance c0 was set to 100% was calculated as the capacitance change rate (ΔCap). The change in ESR caused by the accelerated test was obtained (=r1-r0), and the ratio (%) of the change in ESR when the initial average ESR r0 was set to 100% was calculated as the ESR change rate (ΔESR).
[0139] (b) Weight reduction rate of solid electrolyte layer during heating
[0140] According to the above-described steps, a sample of the solid electrolyte is collected from the solid electrolyte layer of the capacitor element 2 taken out from the solid electrolytic capacitor 1, and the weight reduction rate of the sample is determined.
[0141] 《Solid Electrolytic Capacitor A2》
[0142] A capacitor element and a solid electrolytic capacitor A2 were prepared and evaluated in the same manner as the solid electrolytic capacitor A1 except that 3-hydroxy-6,8-disulfo-2-naphthoic acid represented by the following formula was used instead of 4-hydroxy-5-sulfoisophthalic acid in (3) of the solid electrolytic capacitor A1.
[0143] [Chemical formula 2]
[0144]
[0145] 《Solid Electrolytic Capacitor A3》
[0146] A capacitor element and a solid electrolytic capacitor A3 were prepared and evaluated in the same manner as in the solid electrolytic capacitor A1 except that 5-sulfoisophthalic acid represented by the following formula was used instead of 4-hydroxy-5-sulfoisophthalic acid in (3) of the solid electrolytic capacitor A1.
[0147] [Chemical formula 3]
[0148]
[0149] 《Solid Electrolytic Capacitor B1》
[0150] A capacitor element and a solid electrolytic capacitor B1 were prepared and evaluated in the same manner as in the solid electrolytic capacitor A1 except that 5-sulfosalicylic acid represented by the following formula was used instead of 4-hydroxy-5-sulfoisophthalic acid in (3) of the solid electrolytic capacitor A1.
[0151] [Chemical formula 4]
[0152]
[0153] 《Solid Electrolytic Capacitor B2》
[0154] A capacitor element and a solid electrolytic capacitor B2 were prepared and evaluated in the same manner as the solid electrolytic capacitor A1 except that 2-naphthalenesulfonic acid represented by the following formula was used instead of 4-hydroxy-5-sulfoisophthalic acid in (3) of the solid electrolytic capacitor A1.
[0155] [Chemical formula 5]
[0156]
[0157] Table 1 shows the evaluation results of the solid electrolytic capacitors A1 to A3, B1, and B2.
[0158] [Table 1]
[0159]
[0160] As shown in Table 1, in the Examples where the weight reduction rate of the solid electrolyte was 3% or less, the changes in capacitance and ESR after the reflow process of the solid electrolytic capacitor were significantly reduced compared to the Comparative Examples where the weight reduction rate exceeded 3%.
[0161] 《Solid Electrolytic Capacitors A4~A6》
[0162] In (3) of solid electrolytic capacitor A1, capacitor elements and solid electrolytic capacitors A4 to A6 were produced in the same manner as solid electrolytic capacitor A1, except that the dopant components shown in Table 2 were used instead of 4-hydroxy-5-sulfoisophthalic acid. The capacitor elements or solid electrolytic capacitors were used to perform the evaluations of (6) (a) and (b), and the following (c) evaluation of the airtightness reduction rate was performed.
[0163] (c) Airtightness reduction rate
[0164] After the solid electrolytic capacitor is reflowed, it is cooled to 25°C. The reflow treatment is carried out under the conditions of a peak temperature of 260°C, a holding time of 10 seconds at the peak temperature, and a holding time of 140 seconds above 220°C. After a total of 3 reflow treatments and cooling to 25°C, the solid electrolytic capacitor is immersed in Fluorinert (fluorine-based inactive liquid, manufactured by 3M) heated to 120°C for 30 seconds. At this time, the generation state of bubbles from the solid electrolytic capacitor is confirmed. A total of 20 solid electrolytic capacitors are evaluated, and the number of solid electrolytic capacitors that generate bubbles is evaluated as the airtightness reduction rate.
[0165] 《Solid Electrolytic Capacitor B3》
[0166] In (3) of solid electrolytic capacitor A1, the dopant component shown in Table 2 was used instead of 4-hydroxy-5-sulfoisophthalic acid. The concentration of the dopant component in the aqueous solution was set to 0.5 mol / L. The polymerization voltage of the electrolytic polymerization was set to 4 V (polymerization potential relative to the silver reference electrode). In addition, a capacitor element and a solid electrolytic capacitor B3 were prepared in the same manner as the solid electrolytic capacitor A1. The capacitor element or the solid electrolytic capacitor was used to evaluate (6) (a) and (b), and the airtightness reduction rate of the above (c) was evaluated.
[0167] The evaluation results of the solid electrolytic capacitors A4 to A6 and B3 are shown in Table 2. The results of the similar evaluation of the solid electrolytic capacitors A1, A3, B1, and B2 are also shown in Table 2.
[0168] [Table 2]
[0169]
[0170] As shown in Table 2, when the weight reduction rate of the solid electrolyte is 3% or less, the changes in capacitance and ESR after the solid electrolytic capacitor is subjected to the reflow process are significantly reduced compared to the case where the weight reduction rate exceeds 3%.
[0171] When the weight reduction rate of the solid electrolyte exceeds 3%, the airtightness decreases significantly when exposed to high temperature (B1~B3). When the dopant component satisfies (m1-m2)≥2, the weight reduction rate of the solid electrolyte tends to decrease to below 3% (comparison of A1, A3~A6 and B1~B3). In addition, when the dopant component has an electron-donating functional group (or a third functional group), there is a tendency for the weight reduction rate of the solid electrolyte to further decrease (comparison of A1 and A3). However, the weight reduction rate of the solid electrolyte not only depends on the type of dopant component, but also has a great influence on the polymerization conditions of the solid electrolyte (comparison of A3 and B3).
[0172] The present invention has been described according to the present preferred embodiments, but such disclosure should not be interpreted in a limiting manner. By reading the above disclosure, various modifications and changes are undoubtedly obvious to those skilled in the art belonging to the technical field of the present invention. Therefore, without departing from the true spirit and scope of the present invention, the attached claims should be interpreted as including all modifications and changes.
[0173] Industrial Applicability
[0174] According to the present invention, a solid electrolytic capacitor element and a solid electrolytic capacitor having excellent thermal stability are provided. In addition, the reduction in the airtightness of the solid electrolytic capacitor in the reflow soldering process can also be suppressed. Therefore, the solid electrolytic capacitor element and the solid electrolytic capacitor can be used for various applications requiring high reliability.
[0175] Description of Reference Numerals
[0176] 1: solid electrolytic capacitor, 2: capacitor element, 3: resin outer casing, 4: anode terminal, 4S: main surface of anode terminal, 5: cathode terminal, 5S: main surface of cathode terminal, 6: anode body, 7: dielectric layer, 8: cathode body, 9: solid electrolyte layer, 10: cathode lead layer, 11: carbon layer, 12: metal paste layer, 13: separation layer, 14: adhesive layer.
Claims
1. A solid electrolytic capacitor element comprising an anode body, a dielectric layer formed on a surface of the anode body, and a cathode portion covering at least a portion of the dielectric layer, The cathode portion includes a solid electrolyte layer covering at least a portion of the dielectric layer. Based on thermogravimetric analysis, the solid electrolyte constituting the solid electrolyte layer is heated to 180° C., maintained at 180° C. for 20 minutes, cooled from 180° C. to 30° C., and then heated from 30° C. to 260° C. at a rate of 20° C. / min. The weight loss rate is less than 3%. The solid electrolyte layer comprises a conductive polymer and a dopant component, The dopant component comprises an aromatic compound having multiple functional groups on an aromatic ring, The plurality of functional groups include electron-withdrawing functional groups and may or may not include electron-donating functional groups, In the aromatic compound 1 molecule, when the number of the electron-withdrawing functional groups is m1 and the number of the electron-donating functional groups is m2, (m1−m2)≧2. 2 . The solid electrolytic capacitor element according to claim 1 , which satisfies m2≤1.
3. The solid electrolytic capacitor element according to claim 1, wherein The aromatic compound has at least one first functional group: a sulfonic group as the electron-withdrawing functional group.
4. A solid electrolytic capacitor element comprising an anode body, a dielectric layer formed on a surface of the anode body, and a cathode portion covering at least a portion of the dielectric layer, The cathode portion includes a solid electrolyte layer covering at least a portion of the dielectric layer. The solid electrolyte layer comprises a conductive polymer and a dopant component, The dopant component comprises an aromatic compound, wherein the aromatic compound has an electron-withdrawing functional group and an electron-donating functional group on an aromatic ring. The aromatic compound has at least a first functional group: a sulfonic group and a second functional group: a carboxyl group as the electron-withdrawing functional group, and a third functional group: at least one selected from a hydroxyl group and an alkoxy group as the electron-donating functional group. In the aromatic compound 1 molecule, when the number of the first functional group is n1, the number of the second functional group is n2, and the number of the third functional group is n3, n1≥1, n2≥1, n3≥1, and (n1+n2+n3)≥4, Based on thermogravimetric analysis, the solid electrolyte constituting the solid electrolyte layer is heated to 180°C, maintained at 180°C for 20 minutes, cooled from 180°C to 30°C, and then heated from 30°C to 260°C at a rate of 20°C / min, with a weight loss rate of less than 3%.
5. The solid electrolytic capacitor element according to claim 4, wherein: The aromatic compound has a benzene ring as the aromatic ring, The second functional group is located at a meta position relative to the first functional group. 6 . The solid electrolytic capacitor element according to claim 4 , which satisfies at least one of n1 ≥ 2 and n2 ≥ 2. 7 . The solid electrolytic capacitor element according to claim 4 , wherein n3≧2 is satisfied.
8. The solid electrolytic capacitor element according to claim 4 or 5, wherein: The alkoxy group has 1 to 4 carbon atoms.
9. The solid electrolytic capacitor element according to any one of claims 3 to 5, wherein: The aromatic compound has a benzene ring as the aromatic ring, The electron donating functional group is located at an ortho position or a para position relative to the first functional group.
10. The solid electrolytic capacitor element according to claim 3 or 4, wherein: The aromatic compound has a naphthalene ring as the aromatic ring, and has the first functional group at at least one selected from the 2nd position, 3rd position, 6th position, and 7th position of the naphthalene ring.
11. The solid electrolytic capacitor element according to claim 1 or 4, wherein: The weight reduction rate is 2.5% or less. 12 . A solid electrolytic capacitor comprising at least one solid electrolytic capacitor element according to claim 1 .
Citation Information
Patent Citations
Electropolymerized liquid for conductive polymer formation and method of manufacturing solid electrolytic capacitor using the same
JP2014175424A
Oxidant solution for manufacturing conductive polymer, and method for manufacturing solid electrolytic capacitor by use thereof
JP2014225538A